Analisis Data Mining Menggunakan Algoritma C 4.5 Dalam Memprediksi Penerima Bantuan Sosial - Yemi, Leonardo; Defit, Sarjon; Sumijan, S (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
Poverty is one of the highest problems most often experienced by various developing countries, there are many ways to overcome the purpose of social assistance is to overcome poverty, social assistance is usually provided by the government and non-profit organizations to groups of people who have economic limitations. The purpose of this study was to help recipients of social assistance to be right on target and can help people with limitations. One of the techniques used in data analysis is data mining. This study identifies recipients of social assistance using data mining efficiently and fairly. and testing the rapidminer application in the prediction process using the C4.5 algorithm. This research dataset uses 80 data based on data on recipients of social assistance in the Jati sub-district, Padang city. The results of the C4.5 algorithm performance test were able to present prediction analysis output with a very good level of accuracy, namely 93.75%. These results are quite evident that the C4.5 algorithm is able to present maximum prediction output in determining recipients of social assistance in the Jati sub-district, Padang city for the next period. Based on these results, it can facilitate and accelerate decision-making related to determining the receipt of social assistance by applying the C4.5 algorithm and can provide more accurate results.